Rilettura di še-le-raglô nell’epigrafe venosina di Paregorio ben Teodoro dell’anno 829/830 - Perani, Mauro (Sefer yuḥasin ספר יוחסין | Review for the History of the Jews in South Italy | Rivista per la storia degli ebrei nell’Italia meridionale, 2018)
In questa nota, l’autore intende chiarire il significato di un’espressione ebraica, risultata sinora di difficile comprensione, nell’iscrizione funeraria di Paregorio figlio di Teodoro, che si trova presso la chiesa della Trinità di Venosa. La crux interpretum consiste dell’espressione še-le-raglô, che vi è incisa alla penultima linea e il cui significato letterale sarebbe "sui sui passi, ai suoi piedi". Nella prima metà del XX secolo, Umberto Cassuto ha proposto almeno due possibilità d’interpretazione, suggerendo l’integrazione di un verbo, che sarebbe andato perduto. Accogliendo l’esistenza di questo verbo mancante, si propone qui di tradurre še-le-raglô come: “Che in vista del suo cammino” o “Che al suo camminare”, riferito all’avviarsi del defunto verso un oggetto non specificato (il Gan Eden), mentre il verbo cancellato sarebbe yibbaneh, “possa essere ricostruito”, da collegarsi alla "Casa del Santo dei Santi", ossia il Tempio di Gerusalemme, menzionato alla linea successiva. A New Reading of še-le-raglô in the Epitaph of Paregorios ben Theodoros from Venosa of the Year 829/830 In this note, the author attempts to clarify a word that has resulted difficult to understand by previous scholars. The word appears in the funerary inscription of Paregorios, son of Theodoros, which is still extant outside the Trinity church in Venosa. The word that constitutes the crux interpretum is še-le-raglô, engraved in the penultimate line. Literally meaning “at his footstep, at his foot”, in the first half of the 20th century, its first interpreter and editor, Umberto Cassuto, made at least two attempts to understand its meaning integrating it with another word, a verb, which has been deleted. The new proposal is to translate še-le-raglô as follows: “May be that on the occasion of his walking” or “That while he moves his steps”, referring to the deceased with an implicit object (towards the Gan Eden); the word erased should be yibbaneh, “may be reconstructed”. This reading offers a good understanding of the following last line: “the House of the Saint of Saints”, that is, the Temple of Jerusalem.